2022
DOI: 10.1111/1475-6765.12560
|View full text |Cite
|
Sign up to set email alerts
|

It's about the type of career: The political ambition gender gap among youth wing members

Abstract: One of the main supply-side explanations for women's underrepresentation in politics is the gender gap in nascent political ambition. While this has been examined in terms of electoral ambition, the aspiration to pursue non-electoral careers within parties has been overlooked. In our study, we therefore investigate whether both types of ambition -electoral and non-electoral -vary among young women and men participating in a key entry point for political careers in Western democracies: party youth wings. To do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Ammassari et al (2022) suggest that the reason why young women are less likely to pursue elected political positions is due to gender expectations that women are more likely to be penalized for wanting political power than men and that women are socialized into acting behind the scenes rather than center stage. The study from Ammassari et al (2022) shows that not only can context be an influence but is also shows the importance of including the influence of gender roles when exploring context as a factor.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ammassari et al (2022) suggest that the reason why young women are less likely to pursue elected political positions is due to gender expectations that women are more likely to be penalized for wanting political power than men and that women are socialized into acting behind the scenes rather than center stage. The study from Ammassari et al (2022) shows that not only can context be an influence but is also shows the importance of including the influence of gender roles when exploring context as a factor.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ammassari et al (2022) found that small differences in a political context combined with perception of gender roles can influence young women's desire to pursue a career in politics. By examining the nascent political ambition of young wing party members, they found that men and women are equally interested in pursuing a non-electoral political career, but when it comes to elected political positions, men are more interested to pursue these than women (Ammassari et al, 2022) despite being in the same political context.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many barriers exist to women's access to elected office, but one oft-cited cause of men's political overrepresentation is their greater propensity to run for office. An important body of scholarship has identified this gender gap in nascent political ambition in the US (Fox and Lawless 2004; Fox and Lawless 2010) and globally (Allen and Cutts 2020; Ammassari, McDonnell, and Valbruzzi 2022; Coffé and Davidson-Schmich 2020; Foos and Gilardi 2020; Pruysers, Thomas, and Blais 2020). Generally, scholars find that women are less likely than men to express initial interest in running for office and that this reluctance persists even after controlling for family responsibilities and professional credentials (Bernhard, Shames, and Teele 2021; Kanthak and Woon 2015; Pate and Fox 2018; Preece and Stoddard 2015; Schneider et al 2016).…”
mentioning
confidence: 99%